Rastreamento precoce do transtorno do espectro autista e prevalência em pré-escolares - Roso, Gabriela Simões (2024)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder, characterized by deficits in verbal or non-verbal language, social interaction, communication and the individual's cognitive development. Generally, the diagnosis is made in childhood. Its etiology is still unknown, but there is evidence that genetic and environmental factors are highly influential. The diagnosis of ASD is carried out using a base of behavioral criteria listed in the DSM-V, together with the help of characterization and screening objects. The present work is also justified by the significant increase, on a global scale, in the investigation of the diagnosis of ASD in children, especially in the first years of life, in addition to the researcher's approach to the chosen theme, which she observes, in her clinical experience, a significant increase in children with ASD. From this perspective, the study aims to analyze the epidemiological profile and prevalence of children who show early signs of Autism Spectrum Disorder. The study is of crosssectional, population-based analytical origin, carried out with children aged 16 to 30 months, enrolled in the municipality's early childhood education schools during the data collection period; 65 children were screened. The instrument used for screening was the Modified Checklist for Autism in Toddlers (M-CHAT) as well as an instrument for characterizing and screening Special Health Needs (NES). Those who responded were those responsible for preschool children aged 16 to 30 months, accessed through telephone contact, provided by those responsible for the schools. 65 children were screened, and the screening prevalence was 30%. No characterization variable showed a significant difference for the studied population, those with risk screening, when compared to the others. The studied population showed a 20% prevalence of NES and the screen time of this population is above the recommended level. Therefore, the present study brought new data in the health area on Autism Spectrum Disorder, to the municipality of Palmeira das Missões. The research has some limitations to be considered, mainly the partial inclusion of daycare centers and reduced sampling. However, the application of these characterization objects is necessary for the correct investigation and early tracking of ASD cases in the municipality.